2010
DOI: 10.1038/ijo.2009.280
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of both number and proliferative activity of human endothelial progenitor cells in obesity

Abstract: Objective: Circulating endothelial progenitor cells (EPCs), responsible for neoangiogenesis and vascular repair, negatively correlate with vascular dysfunction and atherosclerotic risk factors. Because obesity may have a crucial role in the development of endothelial dysfunction, this study evaluated the number and proliferative activity of circulating human EPCs in obese (body mass index (BMI) ¼ 48±9, n ¼ 45) compared with lean (23±2, n ¼ 45) volunteers. Methods: EPCs were quantified after isolation of periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 40 publications
3
41
1
2
Order By: Relevance
“…They also reported that, EPCs colony formation was significantly less in the obese and overweight compared with normal weight adults . Another study by Tobler K, et al [67] reported decreased number and premature senescence of EPCs in obese volunteers which could function as early contributors to the development and progression of vascular dysfunction in obesity. In overweight adolescents, the number of CD34-negative EPCs, but not CD34-positive EPCs was reported to be higher which could indicate higher risk for future cardiovascular disease in obese teenagers [68].…”
Section: Impairment Of Epcs Number and Function In Obesitymentioning
confidence: 97%
“…They also reported that, EPCs colony formation was significantly less in the obese and overweight compared with normal weight adults . Another study by Tobler K, et al [67] reported decreased number and premature senescence of EPCs in obese volunteers which could function as early contributors to the development and progression of vascular dysfunction in obesity. In overweight adolescents, the number of CD34-negative EPCs, but not CD34-positive EPCs was reported to be higher which could indicate higher risk for future cardiovascular disease in obese teenagers [68].…”
Section: Impairment Of Epcs Number and Function In Obesitymentioning
confidence: 97%
“…К настоящему времени установлено, что повы-шение сывороточного уровня таких сигнальных мо-лекул, как СРБ и хемокина -протеина, стимулиру-ющего миграцию макрофагов (MСР-1), достоверно ассоциировано с пожилым возрастом [17]. Ведущи-ми причинами, вызывающими повышение уровней VEGF в кровотоке здорового человека с возрастом, являются провоспалительный цитокиновый сдвиг, оксидантный стресс и ишемия.…”
Section: результаты и обсуждениеunclassified
“…È stato infatti dimostrato che i pazienti obesi, rispetto ai controlli normopeso esibiscono un ridotto numero ed anche una ridotta funzionalità delle CEP e che questo effetto di riduzione aumenta con l'aumentare dell'indice di massa corporea [37,38].…”
Section: Riduzione Del Pesounclassified